Experimental Study to Verify the Effect of Parameters on the Depth of Osmotic Heating with 9XC Hardened Steel after Laser Assisted - Nguyen, Thanh Huan; Tran, Xuan Thai; Nguyen, Duc Toan (Old Journal, 2018)
Laser assisted turning (LAT) is using a laser beam to preheat the workpiece before turning [1]. In order to verify the influences of parameters on the depth of osmotic heating after laser heating 9XC hardened alloy steel (62 HRC hardness), various parameters such as: laser power, distance of laser tip to the workpiece, laser position, cutting speed and feed rate had been sellected using Taguchi experimental method. The results shows that the laser power is strongly affect to the depth of osmotic heating of 91,27 % comparing with the others of laser source's parameters. Besides that the effect of cutting parameters on depth of osmotic heating was 95,69 % of cutting speed and 4,31 % of feed rate, respectively. From experimental results, a formula for the surface layer as a function of laser power and cutting speed had also been constructed. Results confirmed that permeability characteristic shows a minor change with increasing of cutting speed, whereas laser power demonstrates a significant effect on permeability characteristic.